Penerapan Kuis Online Wordwall Terhadap Hasil Belajar Peserta Didik Pada Mata Pelajaran IPA Kelas III Madrasah Ibtidaiyah - Ziana Elisa Priscillia; Eli Mufidah (PUSAT PENELITIAN DAN PENGABDIAN KEPADA MASYARAKAT (P3M) SEKOLAH TINGGI ILMU TARBIYAH AL-FATTAH SIMAN LAMONGAN, 2023)
Wordwall online quiz is an online quiz application that is often the teacher's choice to make it easier to understand concepts or learning material through quizzes/evaluation templates in questions. The purpose of this study was to determine 1) the application of online wordwall quizzes on student learning outcomes in science subjects for class III. 2) student learning outcomes in class III science subjects. 3) the effect of the online wordwall quiz on student learning outcomes in science subjects for class III. This research is quantitative through the method of pre-experimental design type one group pretest-posttest (initial test - single group final test). Data collection methods used are : observation, Questionnaire and test. The data analysis techniques used are desccriptive analysis, normality test, and hypothesis testing. Based on the results of data analysis, it can be concluded that : 1) The implementation of learning using the Online Quiz Wordwall has an average implementation of 93,33% with very good criteria. 2) ) student learning outcomes obtained in the pre-test get an average score of 54.28 while the post-test gets an average score of 85.71, indicating that the application of online wordwall quizzes is good for use in learning. 3) there is an influence with the application of of the online wordwall quiz on the learning outcomes of class III students on animal growth and development as evidenced by the